2015
DOI: 10.1007/s11090-015-9627-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Temperature Plasma on the Structure of Seeds, Growth and Metabolism of Endogenous Phytohormones in Pea (Pisum sativum L.)

Abstract: The objective of this study was to determine the influence of low-temperature plasma (LTP) on seed surface modification, water uptake by seeds, seed germination and vigor of seedlings, as well as changes in the content of endogenous hormones in pea, (Pisum sativum L. var. Prophet). The study's authors used diffuse coplanar surface barrier discharge as the source of LTP in various duration times of treatment (from 60 to 600 s). The SEM analysis showed that LTP induced significant changes on the seeds' surface, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
162
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(185 citation statements)
references
References 37 publications
14
162
1
Order By: Relevance
“…Numerous studies have suggested that there might be some association between seed germination and water uptake, and the water uptake of seeds would benefit seed germination and seedling growth [Volin et al, ; Stolarik et al, ]. Our study found that DBD plasma treatments enhanced the water uptake of wheat seed (Table ), and these results were consistent with the findings of Filatova et al [], who observed that the cold plasma treatment could improve the water uptake of some grains and legumes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Numerous studies have suggested that there might be some association between seed germination and water uptake, and the water uptake of seeds would benefit seed germination and seedling growth [Volin et al, ; Stolarik et al, ]. Our study found that DBD plasma treatments enhanced the water uptake of wheat seed (Table ), and these results were consistent with the findings of Filatova et al [], who observed that the cold plasma treatment could improve the water uptake of some grains and legumes.…”
Section: Discussionsupporting
confidence: 91%
“…Sera et al [] found that microwave plasma could increase wheat and oat germination. Stolarik et al [] concluded that pea seed treated by high‐frequency plasma significantly improved its germination rate. However, these results were not consistent with those reported by Volin et al [], who observed that corn and bean seed germination were inhibited after a fluorocarbon plasma treatment, and attributed these phenomena to a plasma‐deposition of hydrophobic materials on the seed coats.…”
Section: Discussionmentioning
confidence: 99%
“…Also reactive nitrogen species, such as NO or NO 2 ‾, and NO 3 ‾, can stimulate germination in broad range of plant species and break seed dormancy . Several models had been proposed to determine NO 3 ‾ role in germination and conclude that the RONS signaling involve interactions with endogenous phytohormones by affecting abscisic acid levels in imbibed seeds or by enhancing gibberellic acid synthesis . In order to clarify the mechanism of the PAW effect on germination in more details, it would be necessary also to analyze activity of hydrolytic enzymes affecting germination rate and initial plant development.…”
Section: Resultsmentioning
confidence: 99%
“…6c. After plasma processing, the highly compact surface texture of the seed coat may also be more fragile, and hence easier to crack, which would facilitate the more efficient absorption of water and nutrients 2 .
Figure 6Representative SEM images of the surfaces of ( a ) untreated cotton seeds and ( b , c ) cotton seeds treated for 27 min with N 2 plasma. Treatment of seeds with N 2 plasma resulted in thinning of the ridges and the presence of a larger number of thin grooves, which was labeled by arrows.
…”
Section: Resultsmentioning
confidence: 99%